Fatal Progressive Meningoencephalitis Diagnosed in Two Members of a Family With X-Linked Agammaglobulinemia - Kasahara, Yasushi; Imamura, Masaru; Shin, Chansu; Shimizu, Hiroshi; Utsumi, Jirou; Hosokai, Ryosuke; Iwabuchi, Haruko; Takachi, Takayuki; Kakita, Akiyoshi; Kanegane, Hirokazu; Saitoh, Akihiko; Imai, Chihaya (Frontiers in Pediatrics, 2020)
Chronic enteroviral meningoencephalitis is a well-known complication in patients with X-linked agammaglobulinemia (XLA). However, progressive neurodegenerative disorders or chronic neuroinflammatory diseases with no causative microorganisms have been recognized as rare central nervous system (CNS) complications in XLA. We herein report a family in which two of three members with XLA had developed progressive meningoencephalitis with an unknown etiology. A 15-month-old male infant presented with left-sided ptosis. Initially, the family denied any family history of inherited diseases, but later disclosed a family history of agammaglobulinemia previously diagnosed in two family members. In the early 1980s, one of the elder brothers of the index patient’s mother who had been treated with intramuscular immunoglobulin [or later intravenous immunoglobulin (IVIG)] for agammaglobulinemia deceased at 10 years of age after showing progressive neurological deterioration during the last several years of his life. The index patient was diagnosed with XLA caused by Bruton tyrosine kinase deficiency (654delG; Val219Leufs*9), and chronic meningoencephalitis with an unknown infectious etiology. Magnetic resonance imaging of the brain demonstrated inflammatory changes in the basal ganglia, hypothalamus, midbrain, and pons, with multiple nodular lesions with ring enhancement, which showed impressive amelioration after the initiation of IVIG replacement therapy. Pleocytosis, which was characterized by an increase in CD4-positive and CD8-positive T cells expressing an activation marker and an elevation in inflammatory cytokines in the cerebrospinal fluid, was identified. No microorganism was identified as a cause of CNS complications. He thereafter developed brain infarction at 19 months of age and fatal status epilepticus at 5 years of age, despite regular IVIG with high trough levels and regular intraventricular immunoglobulin administration. The etiology of this rare CNS complication in XLA is currently unknown. Previous studies have suggested a possible association of IVIG, which was clearly denied in our index case because of the demonstration of his neurological disorder at presentation. In the future, extensive and unbiased molecular methods to detect causative microorganisms, as well as to investigate the possible role of autoimmunity are needed to clarify the etiology of CNS complications.